Does Military Spending Matter for Long-run Growth?. Issue 4 (4th July 2017) - d'Agostino, Giorgio; Dunne, J. Paul; Pieroni, Luca
Abstract: The effects of military spending has on the economy continues to be a subject of considerable debate, with a lack of consensus in the literature. This paper takes advantage of the Stockholm International Peace Research Institute extended data-set to contribute to the debate using empirical methods made available, or more applicable, by the extra observations. It constructs a large panel of countries for the period 1970–2014 to explore the long-run equilibrium relationship between military spending and economic growth, applies the more flexible pooled mean group estimator, and compares the results with the more restrictive dynamic fixed effect method used in earlier influential studies. It also compares results from different time and country samples. Across the specifications it finds a significant and persistent negative effect of military burden on economic growth that is robust across different country groups, with the largest impact being for OECD countries.